Preservation and Revitalization of Hybrid Scripts of Traditional Muslim Communities: A Study of Arabi-Malayalam - KP, Hassan Shareef; Khan, Shebeeb (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2025)
This study examines the preservation and revitalization of Arabi-Malayalam, a unique hybrid script combining Arabic script with the Malayalam language, historically used by the Mappila Muslim community in Malabar, Kerala, India. This research addresses the decline of Arabi-Malayalam due to sociocultural changes, educational reforms, and religious movements, highlighting its significance in maintaining cultural identity and heritage. Employing a qualitative, literature-based methodology, this study analyzes historical developments, cultural contexts, and comparative cases of endangered language preservation. It identifies the rich literary and scientific contributions of Arabi-Malayalam and the challenges posed by its diminishing use among the region’s younger generations. This study proposes multifaceted strategies for revitalization, including community engagement, educational initiatives, technological integration, and institutional support, to ensure the script’s continued relevance. The findings emphasize the importance of balancing tradition and modernity, advocating for Arabi-Malayalam as a complementary cultural asset alongside standard Malayalam. This revitalization effort not only preserves a vital link to the Mappila community’s past but also fosters cultural pride, intellectual advancement, and social cohesion in contemporary world.